THE IMPACT OF INTERIOR LIGHTING ON HEALTH AND VISUAL COMFORT (World Science, 2025)
Light is being increasingly utilized as a therapeutic intervention, with numerous studies documenting specific cases of its application. Despite its potential benefits, it is crucial to acknowledge the risks associated with adverse side effects. Interior lighting not only defines the aesthetic perception of a space but also plays a fundamental role in shaping human physiological and psychological well-being.Scientific research has demonstrated that light stimulation can contribute to the improvement of various physiological and psychological conditions, including depressive disorders and sleep disturbances such as insomnia. Conversely, inadequate lighting may lead to headaches, visual fatigue, general exhaustion, and even disruptions in vitamin D synthesis.This study examines the impact of lighting on human health and explores strategies for optimizing lighting design to enhance visual comfort and boost productivity. The color temperature of light is a critical factor in this context: warm-toned lighting fosters a sense of comfort and relaxation, whereas cooler light enhances concentration and cognitive performance.To minimize the adverse effects of lighting, it is advisable to use luminaires with adjustable brightness and color temperature, as well as to maximize the integration of natural light into interior spaces. Additionally, reducing glare, ensuring the appropriate placement of light sources, and minimizing flicker in fluorescent lighting are essential measures for improving visual comfort.Interior lighting should not be regarded solely as an aesthetic element but rather as a crucial determinant of human health and efficiency. An optimized lighting design can significantly enhance quality of life and prevent a range of health issues associated with poor lighting conditions.